Asymmetric Amination of α‐Chiral Aliphatic Aldehydes via Dynamic Kinetic Resolution to Access Stereocomplementary Brivaracetam and Pregabalin Precursors. Issue 4 (21st December 2017) - Fuchs, Christine S.; Farnberger, Judith E.; Steinkellner, Georg; Sattler, Johann H.; Pickl, Mathias; Simon, Robert C.; Zepeck, Ferdinand; Gruber, Karl; Kroutil, Wolfgang
Abstract: Over the last decades biocatalysis has emerged as an indispensable and versatile tool for the asymmetric synthesis of active pharmaceutical ingredients (APIs). In this context, especially transaminases (TAs) have been successfully used for the preparation of numerous α‐chiral, optically pure amines, serving as important building blocks for APIs. Here we elaborate on the development of transaminases recognizing the α‐chiral centre adjacent to an aldehyde moiety with aliphatic residues, opening up concepts for novel synthetic routes to the antiepileptic drugs Brivaracetam and Pregabalin. The transformation proceeded via dynamic kinetic resolution (DKR) based on the bio‐induced racemisation of the aldehyde enantiomers, enabling the amination of the racemic substrates with quantitative conversions. Medium, substrate as well as enzyme engineering gave access to both ( R )‐ and ( S )‐enantiomers of the amine precursors of the stereocomplementary drugs in high optical purity, representing a short route to mentioned APIs. Abstract :